Nitrogen-doped bismuth molybdenum carbide: A superior heterojunction catalyst for electrochemical nitrite sensing in food - Maroua Saadaoui (20090805) (2025)
In this work, we developed a high-performance electrochemical sensor for sensitive and selective detection of nitrite in environmental and food samples, utilizing bismuth-modified nitrogen-doped molybdenum carbide nanocomposites (Bi@N-Mo₂C) as the active material The nanocomposite was synthesized through a two-step process involving the formation of Bi@PD-Mo hollow spheres via self-assembly polymerization, followed by thermal carbonization to yield Bi@N-Mo₂C. The resulting material was immobilized on a glassy carbon electrode, enhancing electrochemical activity, as confirmed by Cyclic voltammetry and differential pulse voltammetry through its excellent sensitivity, reproducibility, and long-term stability. Sensor exhibited a broad linear detection range (14.9 μM–3.8 mM) and an ultralow detection limit of 0.13 μM. Its practical applicability was demonstrated by successful nitrite detection in real samples including milk, apple juice, and tap-water. The sensor also showed high selectivity and robustness in complex environments, indicating its potential as a reliable platform for food safety and environmental monitoring. Other Information Published in: Food Chemistry License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.foodchem.2025.146087